Eradication of human African trypanosomiasis? Don't forget the pigs! - Roesel, Kristina; Grace, Delia; Mehlitz, D.; Clausen, Peter-Henning (Freie Universität Berlin, 2018)
Animal African Trypanosomosis (AAT) and Human African Trypanosomosis (HAT), caused by a protozoa of the genus Trypanosoma (section Salivaria), are both diseases of significant importance to sub-Sahara Africa. Several species of Trypanosoma are found in Africa but only two subspecies of T. brucei, are relevant to humans. They either cause the chronic (T. b. gambiense) or the acute (T. b. rhodesiense) form of human sleeping sickness, both with a fatal outcome if left untreated. While wildlife have long been known to be reservoirs for both HAT and AAT and show no clinical symptoms, infection in livestock, especially cattle, causes severe losses to local producers and are potential reservoirs for rhodesiense-HAT. Domestic pigs, too, are preferred hosts of Glossina spp. and have been reported to be potential reservoirs of both forms of HAT. Pigs are increasingly important as a source of income and food for smallholder livestock farmers in East Africa, especially in Uganda where both forms of HAT as well as AAT are endemic. Except for T. suis and T. brucei gambiense, all Trypanosoma species known to infect pigs have been reported from pigs in Uganda. The authors present findings from a review on the potential role of pigs as a livestock reservoir for HAT. We will discuss how and why infection with Trypanosoma spp. in pigs should be considered in differential diagnoses in clinically sick animals as well as in national HAT surveillance and eradication programs.